The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1963
DOI: 10.1002/zaac.19633200122
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis von Hydrazin‐Kaolinit

Abstract: In das Schichtengitter des Kaolinits kann Hydrazin reversibel eingelagert werden. Der Schichtabstand erhöht sich dabei von 7,16 Å auf 10,41 Å. Die Einlagerungsgeschwindigkeit wird wesentlich beeinflußt von den noch unbekannten Assoziationsgleichgewichten in der wässerigen Hydrazinlösung. Eine eindimensionale FOURIER‐Projektion auf die Schichtnormale gibt einen Hinweis auf die Anordnung der Hydrazinmolekeln zwischen den Silicatschichten. Kaoline mit den Gitterstörungen des sogenannten Fire‐Clay‐Typs reagieren m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 28 publications
6
45
0
Order By: Relevance
“…After washing the intercalates with water to remove the KAc, he found that kaolinite, dickite, and hydrated halloysite reverted to their original spacings, but that nacrite formed a well-defined hydrate with d(001) equal to 8.35/~. Weiss et al (1963) reported a 8.33-/~ phase formed by the water washing of a kaolinite which had been expanded by urea but did not identify this material as a hydrated phase of kaolinite. By means of KAcand urea-intercalates, van Olphen and Deeds (1963) obtained a 8.45-.~ spacing for a well-defined hydrate of what they considered to be dickite.…”
mentioning
confidence: 98%
“…After washing the intercalates with water to remove the KAc, he found that kaolinite, dickite, and hydrated halloysite reverted to their original spacings, but that nacrite formed a well-defined hydrate with d(001) equal to 8.35/~. Weiss et al (1963) reported a 8.33-/~ phase formed by the water washing of a kaolinite which had been expanded by urea but did not identify this material as a hydrated phase of kaolinite. By means of KAcand urea-intercalates, van Olphen and Deeds (1963) obtained a 8.45-.~ spacing for a well-defined hydrate of what they considered to be dickite.…”
mentioning
confidence: 98%
“…With dimethyl sulphoxide (Weiss et al, 1966;Olejnik et al, 1968;Sanchez Camazano and Gonzalez Garcia, 1966) it was found that the S=O bond was perpendicular to the clay sheets with the oxygen atom 1-8 A from the plane containing the hydroxyl groups, a geometry almost identical to that found for the C = O in formamide. Pyridine N-oxide (Olejnik et al, 1970Weiss and Orth, 1973) also forms an intercalate with kaolinite and the available evidence shows that the molecule has its long axis almost perpendicular to the clay sheets with the oxygen atom at 2.0/~ from the hydroxyl plane.…”
Section: Intercalates With Other Small Moleculesmentioning
confidence: 82%
“…The N-H-9 9 O bond was found to be weaker than the N-H--9 O--C bond in liquid formamide and also the formamide molecules were shown to be at a large angle to the mineral sheets. This last point was also made by Weiss et al (1963) who used a one-dimensional Fourier projection to show that the -NH~ group was near the silicate oxygens of one sheet with the HCO group near the OH's of the neighboring layer. The essential features of the bonding between formamide and the dickite brought out by the structural evaluation were (Figures I, 2): (i) the three hydrogen bonds from the clay hydroxyls to the carbonyl oxygen, (ii) the hydrogen bond from the amide nitrogen to one of these three hydroxyls and (iii) the hydrogen bond from the amide nitrogen to the silicate oxygen of the next sheet.…”
Section: Adamsmentioning
confidence: 82%
“…To our knowledge, the preparation of kaolinite-CTAC complex using U as precursor was not published before. Direct intercalation of U into kaolinite was carried out using solution [1,2,4,8,9,16,20,26,28,34,37,38], mechanochemical (co-grinding) [13, 21-23, 25-28, 31, 32, 37], and homogenization [41] techniques. These techniques resulted in high degree of intercalation, but the mechanochemical and homogenization techniques require less time and consume an order of magnitude less chemicals.…”
Section: Introductionmentioning
confidence: 99%